Pengaruh Persepsi Harga, Kualitas Produk, Dan Citra Merek Terhadap Keputusan Pembelian Romi Bakery Di Kecamatan Medan Polonia - Sugara Panangi Limbong; Indawati Lestari (Journal of Innovative and Creativity, 2025)
The primary objective of this study was to examine and analyze the partial and simultaneous effects of Price Perception, Product Quality, and Brand Image on consumer Purchasing Decisions at Romi Bakery in Medan Polonia District. The intense competition within the bakery industry and the observed sales fluctuations at Romi Bakery underscore the existing uncertainty in consumer behavior, necessitating this research to identify the key driving factors behind purchasing decisions. This research employed an associative quantitative approach. Data were collected via questionnaires distributed to a sample of 85 Romi Bakery consumers. The statistical analysis utilized Multiple Linear Regression, preceded by Validity and Reliability Tests, and Classical Assumption Tests (Normality, Multicollinearity, and Heteroscedasticity). ​The results confirmed that the regression model met all classical assumption criteria. Based on the t-test (partial analysis), it was found that Price Perception, Product Quality, and Brand Image each individually had a positive and significant influence on Purchasing Decisions (Sig. < 0.05). Furthermore, the F-test (simultaneous analysis) verified that all three independent variables collectively exerted a positive and significant influence on Purchasing Decisions. The Coefficient of Determination (R2) test indicated a high combined contribution of the three variables in explaining the variation in Purchasing Decisions. The study concludes that an integrated strategic management approach focusing on value-oriented pricing, improved product quality consistency, and strengthening the brand's visual identity is crucial for Romi Bakery to sustain loyalty and stimulate repeat purchases.